2007
DOI: 10.2320/matertrans.md200717
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Free-Standing Tungsten-Nanowhiskers on SiO<SUB>2</SUB> Substrates with Electron-Beam Induced Deposition

Abstract: Free-standing tungsten-nanowhiskers about 3 nm in thickness were fabricated on SiO 2 substrates with electron-beam induced deposition in a transmission electron microscope operated at 400 kV at room temperature. The growth process of the nanowhisker was observed in-situ and analyzed. The nanowhisker was characterized with high-resolution transmission electron microscopy. Nucleus-deposits smaller than 1 nm formed on the surface of the substrate, grew to 2$3 nm and then grew out of the surface to form nanowhiske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Thus, molecules are attracted to the tip, and the deposit increases in length upon further EB irradiation. The formation of W nanodot deposits on the surface of a SiO 2 substrate and the growth of W nanowhiskers from these nanodots [20] are consistent with the above mechanism. The growth of a nanobush can also be understood qualitatively on the basis of the above mechanism [19].…”
Section: Growth Mechanisms Of the Nanostructuressupporting
confidence: 69%
See 2 more Smart Citations
“…Thus, molecules are attracted to the tip, and the deposit increases in length upon further EB irradiation. The formation of W nanodot deposits on the surface of a SiO 2 substrate and the growth of W nanowhiskers from these nanodots [20] are consistent with the above mechanism. The growth of a nanobush can also be understood qualitatively on the basis of the above mechanism [19].…”
Section: Growth Mechanisms Of the Nanostructuressupporting
confidence: 69%
“…It was confirmed that body-centered cubic (bcc) W nanocrystals are contained in as-prepared W nanowhiskers [20] and W nanodendrites [18,[21][22][23] by high-resolution transmission electron microscopy (HRTEM) and selected-area electron diffraction (SAED) or microbeam electron diffraction (MBED). Figure 9 shows HRTEM and SAED images of W nanodendrites [18].…”
Section: Characterization Of the Nanostructuresmentioning
confidence: 82%
See 1 more Smart Citation
“…This may be due to the charged-up electrons, which induced the nonequilibrium chemical decomposition of the precursor gas. It was confirmed that body-centered cubic (bcc) tungsten nanocrystals with an amorphous structure comprised the nanostructures and that the fraction of the crystalline structure increased with increasing energy of the electron beam [17,27,30,31].…”
Section: Growth Of Nanostructures On Insulators By Ebidmentioning
confidence: 57%
“…Thin films of Al 2 O 3 [17][18][19][24][25][26] and SiO 2 [27][28][29][30] were irradiated by an electron beam in TEMs with organometallic precursor gases at room temperature. Figure 2(a) shows a micrograph of the initial stage of the growth of nanostructures under a current density of about 0.75 A cm −2 .…”
Section: Growth Of Nanostructures On Insulators By Ebidmentioning
confidence: 99%